Covid-19 in the hospitality industry workforce: the resilience of hotel workers through human resource empowerment and motivation - Dina Mellita; Sholahudin Arsyad; Andrian Noviardy (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The article aims to summarize the main arguments and counterarguments within the scientific discussion on human resource empowerment and its impact on motivation as the main factor to resilience hotel workers getting through the pandemic Covid-19. The research variables which include human resource empowerment and Motivation in this study are latent so to identify the influence of the independent latent variables on the dependent latent variable, Structural Equation Modeling (SEM) was used. From the respondent's views, the study found out that, on the empowerment construct all statements scored above 3 except credibility. Within a coefficient of determination, it shows that the variation of the motivation variable for hotel workers during the pandemic is 52 percent influenced by human resource empowerment carried out by the management. Therefore, it can be concluded that to strengthen the empowerment of workers through the pandemic, the hotel should strengthen its capacity for worker empowerment within opportunity, delegate, provide for recognition, and create an open communication system to create mutual understanding between employees and management.